Mujeres científicas en enfermedades infecciosas ciencia: hacia una mejor representación e inclusión - Maria Dolores Correa (Asociación Colombiana de Infectología, 2023)
Representation and inclusion of women in Science, Tech-nology, Engineering and Mathematics (STEM) still remain a significant challenge. One significant indicator about this is that only 4% of Nobel prizes have been awarded to women1. UNESCO Science Report shows that only some 33% of researchers around the world are women2. Aware of the under-representation of women in science, in 2015, the United Nations General Assembly declared 11 February as the International Day of Women and Girls in Science3.